(untitled) (Research, Society and Development, 2021)
This study investigates the bibliographic production published in the scientific literature about the influence of stress on absenteeism among secondary and elementary school teachers. To construct the article, we consulted the PubMed, CAPES, and Virtual Health Library-BVS databases, using the descriptors "psychological stress"; "occupational stress"; "psychological burnout"; "sick leave"; "absenteeism"; "school teachers". The inclusion criteria for the articles were subjects related to stress in middle school and elementary school teachers; publications in indexed journals, between 2010 and 2020; and the exclusion criteria were duplicate publications in more than one database. Thus, 11 scientific articles published in Portuguese, English and Spanish were selected. Regarding stress and absenteeism, it was found that these occur due to psychological disorders or psychological suffering associated with work, lack of motivation, drop in productivity, and physical and mental illnesses. About the mechanisms to reduce stress, there is a need for investments in work environments such as the participation of teachers in organizational policies and the creation of prevention policies that contribute to the improvement of teachers’ health. The concern of organizations and educational managers with the emotional health of teachers can reduce absenteeism due to health problems such as occupational stress.